Disasters and Mitigation in Civil Engineering Perspective (Case Study: Flooding Overflow Occurred and Hit Dili, Capital of Timor-Leste on 4th April, 2021) - Gomes, Saturnino (Transactions on Engineering and Computing Sciences, 2025)
Civil engineering disasters refer to failures in infrastructure and construction that result in catastrophic consequences, often leading to loss of life, property damage, and economic setbacks. These disaster can be caused by natural hazards, design flaws, material failures, or human errors. Mitigation strategies in civil engineering focus on designing resilient structures, implementing strict building codes, and using advanced technologies to prevent or minimize disaster impact. This paper presents the concept of civil engineering disasters, their characteristics, classification, causes, and mitigationtechnologies. Civilengineering disasters are caused primarily by civil engineering defects, which are usuallyattributed toimproper selection of construction site, hazard assessment, design and construction, occupancy, and maintenance. Fromthis viewpoint, manynatural disasters such as earthquakes, strong winds, floods, landslides, and debris flowsare substantially due to civil engineering defects rather than the actual natural hazards. Civil engineering disasters occurfrequently and globally and are the most closely related to human beings among all disasters.